2020
DOI: 10.3390/rs12244123
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network to Infer the Mediterranean 3D Chlorophyll-a and Temperature Fields from Remote Sensing Observations

Abstract: Remote sensing data provide a huge number of sea surface observations, but cannot give direct information on deeper ocean layers, which can only be provided by sparse in situ data. The combination of measurements collected by satellite and in situ sensors represents one of the most effective strategies to improve our knowledge of the interior structure of the ocean ecosystems. In this work, we describe a Multi-Layer-Perceptron (MLP) network designed to reconstruct the 3D fields of ocean temperature and chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Works attempting to predict vertical pigment profiles from surface data targeted the Chla and were based on the surface Chla and/or assigned with other physical factors such as SST and currents ( [13,14,[17][18][19][20]). However, during the optimization process of Sat2Profile, we showed that the problem is more complex when dealing with different pigments at the same time, each with their own particular variability.…”
Section: Discussionmentioning
confidence: 99%
“…Works attempting to predict vertical pigment profiles from surface data targeted the Chla and were based on the surface Chla and/or assigned with other physical factors such as SST and currents ( [13,14,[17][18][19][20]). However, during the optimization process of Sat2Profile, we showed that the problem is more complex when dealing with different pigments at the same time, each with their own particular variability.…”
Section: Discussionmentioning
confidence: 99%
“…To tackle this challenge, the relevant gaps reported in Table 2 need to be addressed at first. A required step forward is the integration of satellite observations with the sparse in situ offshore and coastal observations into AI and/or numerical models to bring out the synoptic 4D description of Mediterranean (Sammartino et al, 2020) and its marine coastal areas (Melet et al, 2020). Several scientific challenges still exist related to the need of improving the observing capabilities at small spatial and temporal scales, to capture their variability, to improve model-data integration and uncertainty estimation (Tintoré et al, 2019), and to address the biological and ecological dimensions, which are essential components to meet the society demand.…”
Section: Gapsmentioning
confidence: 99%
“…A deeper understanding of the dynamics and evolution of marine phytoplankton requires three dimensions (3D) observations of the algal abundance at different temporal and spatial scales and much wider and regular coverage than currently achievable (Sammartino et al, 2020). However, the traditional measurement is mainly based on in situ sampling either through coastal monitoring programs or time-limited oceanographic cruises, or fixed platforms such as moored buoys, which can accurately describe local conditions along the water column, but are clearly inadequate to describe processes occurring within the wide range of temporal and spatial scales impacted by undergoing changes (von Schuckmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Result-oriented approach is to infer Chl-a concentration at different depths directly from other measurable ocean variables. Due to the complexity of the marine ecosystem, this kind of method usually requires tools as artificial neural network (Sammartino et al, 2020) and its variants (Puissant et al, 2021), which are capable of revealing non-linear relations. Although the performance of such methods has been validated on regional and even global scale, the huge demand for input variables and computational resources greatly limits their utilization potentiality (Erickson et al, 2019;Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%